The reflection of modern trends of linguistics in Uzbek poetry - Kamolova Sadoqat Jabbor qizi; Boymurodova Marjona Bahodir qizi (Zien Journals, 2022)
This article describes the pragmalingvistic foundations of modern linguistics using anthropocentric trends, how modern approaches to linguistics are reflected in Uzbek poetry
Keywords: anthroposentrizm; pragmalingvestica; tendensiya; paradigm